Values interact with psychological distance and eco-anxiety to promote climate engagement: insights from two experimental studies - Zhang, Hanwen; Xu, Wen; McCauley, Michelle (Frontiers in Psychology, 2025)
The effectiveness of encouraging engagement with climate change through reducing its psychological distance has been increasingly called into question. Through two experimental studies, we examine how value orientation interacts with proximal information and eco-anxiety to affect climate engagement. Study 1 (N = 472) tested how exposure to spatially proximal versus distal messaging conditions affected psychological distance to climate change and subsequent climate risk perception, policy support, and mitigation intention. We found that spatial messaging conditions did not significantly affect psychological distance or climate engagement. However, both self-transcendence values and proximal distance predicted more climate engagement. Additionally, the positive association between proximal psychological distance and pro-environmental behavioral intention was stronger among individuals with higher self-transcendence and weaker among individuals with higher self-enhancement. Study 2 (N = 414) examined whether a self-reflective writing task to invoke eco-anxiety is more effective than proximal messaging at increasing climate engagement. We found that the writing task was more effective than proximal messaging at eliciting eco-anxiety, which positively predicted risk perception, policy support, information sharing intention, and effortful mitigation behavior. Path analysis reveals that stronger self-transcendence values not only directly predicted more climate engagement but also predicted higher eco-anxiety in response to interventions. Collectively, our results suggest that elicitation of eco-anxiety could be a superior strategy for increasing engagement with climate change than exposure to information about its local impacts.